Features of the Party System of the Republic of Equatorial Guinea - GRISHINA Nina Vladimirovna (Ученые записки Института Африки Российской академии наук)
The foundations of political activity were laid in Equatorial Guinea during the colonial era. At that time, several ethnic-based parties were active, advocating the complete separation of the island of Fernando Po from the continental province of Rio Muni. After decolonization in 1968, power was effectively monopolized by the Fang people.